2009
DOI: 10.1111/j.1476-5381.2008.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Ezetimibe reduces plaque inflammation in a rabbit model of atherosclerosis and inhibits monocyte migration in addition to its lipid‐lowering effect

Abstract: Background and purpose: Ezetimibe, a selective inhibitor of intestinal cholesterol absorption, might also suppress inflammatory components of atherogenesis. We have studied the effects of ezetimibe on two characteristics of atherosclerotic plaques (infiltrate and fibrosis) and on expression of inflammatory genes in a rabbit model of accelerated atherosclerosis. Experimental approach: Femoral atherosclerosis was induced by a combination of endothelial desiccation and atherogenic diet. Animals were randomized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 30 publications
2
44
0
1
Order By: Relevance
“…cDNAs were synthesized with 1 g of total RNA, ReverTra Ace (Toyobo, Osaka, Japan), and oligo(dT) [12][13][14][15][16][17][18] primers according to the manufacturer's instructions. 23 Gene expression was measured by real-time PCR on an Applied Biosystems Prism 7500 system (Applied Biosystems, Foster City, CA) using cDNA, real-time PCR Master Mix Reagents (Toyobo), a set of gene-specific oligonucleotide primers, and the TaqMan probes listed in Table 1.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…cDNAs were synthesized with 1 g of total RNA, ReverTra Ace (Toyobo, Osaka, Japan), and oligo(dT) [12][13][14][15][16][17][18] primers according to the manufacturer's instructions. 23 Gene expression was measured by real-time PCR on an Applied Biosystems Prism 7500 system (Applied Biosystems, Foster City, CA) using cDNA, real-time PCR Master Mix Reagents (Toyobo), a set of gene-specific oligonucleotide primers, and the TaqMan probes listed in Table 1.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…[11][12][13][14][15] It decreases the serum levels of low-density lipoprotein cholesterol and triglycerides (TGs) in humans 16 and reduces plaque formation and improves lipids in a rabbit model of atherosclerosis. 17 Recent reports have indicated that ezetimibe improves liver steatosis and insulin resistance in Zucker obese fatty rats 18 and rats fed a methionine-and choline-deficient diet. 19 Thus, ezetimibe is a potential new therapeutic agent for human NASH.…”
mentioning
confidence: 99%
“…This cross-talk may change with age as a result of increased macrophage infiltration of adipose tissue [10]. Interestingly, monocyte-derived macrophage express NPC1L1 and other proteins bound by ezetimibe (amino peptidase N, annexin-2, and caveolin-1) [31,32], while ezetimibe was found to reduce the number of monocytes and the expression of monocyte chemoattractant protein-1 (MCP-1) in atherosclerotic plaques in rabbits [33]. It is possible that age-related changes in the number and function of macrophages may, at least partially, contribute to the different effect of ezetimibe in various age groups.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of ezetimibe on the development of atherosclerosis was first shown in apolipoprotein E-deficient mice fed with a highfat diet [5] . Similarly, ezetimibe reduced atherosclerotic lesion formation in a diet-induced atherosclerosis model in hypercholesterolemic rabbits [6] . However, the exact anti-atherosclerotic mechanism of ezetimibe remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%